PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WORD WALL TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN SBDP KELAS V - KUNTI, KUNTI SHOUMA TSANIYA; Atip Nurharini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the cooperative learning model Teams Games Tournament (TGT) assisted by Word Wall media on students' learning interest in Cultural Arts and Crafts (SBDP), specifically in the dance aspect for fifth-grade students at SD Negeri Tlogosari Wetan 01. The background of this research is the low learning interest among students caused by conventional teaching methods that lack active student involvement. The research employed a quantitative approach with a quasi-experimental design using the Nonequivalent Control Group Design. The sample consisted of two classes: class VA as the experimental group and class VB as the control group, each with 22 students. Data collection instruments included questionnaires, observation, documentation, and interviews. Data analysis using the independent samples t-test revealed a significant difference in learning interest between the experimental and control groups, with a significance value of 0.028 (< 0.05). The average posttest score of students’ learning interest in the experimental class was higher than that of the control class. The findings conclude that the TGT learning model assisted by Word Wall media significantly enhances students' learning interest in SBDP, particularly in traditional dance learning.